Inventario de Avifauna del cantón San Lorenzo provincia de Esmeraldas - Angulo Quintero, Yadira Katherine (2021)
The present research was carried out with the purpose of obtaining an inventory of avifauna in the canton of San Lorenzo, from the province of Esmeraldas; due to the importance of birds and their potential for tourism development, it was determined important to know the species of birds and their conservation status. For which it was defined to make a diagnosis of the study area, through the bibliographic and documentary review, complemented with field outings, which allowed to know the characteristics of the sector, ecosystems present, altitude, presence of water bodies, determining areas for bird monitoring; obtaining two zones for this, the first in the El Muelle sector, also known as the Ecoregion of Chocó Biogeográfico, adjacent to the Cayapas Mataje Mangroves Ecological Reserve, and zone two the parish Yalaré that corresponds to a tropical humid forest intervened by palm trees and crops, where the Yalares Protective Forest is located. Once the zones have been determined, means of recording were established mainly using the point-by-point method, in transects located in each of the zones, where the search and registration of species was carried out during the morning hours (from 5h00 to 10h00), during the field departure the photographic record was made and as far as possible the taxonomic records were completed; subsequently, the information was systemtized and a total of 40 species of birds recorded were identified, of which 33 were registered in zone 1 and 32 in zone 2. According to the conservation status of the species proposed by the International Union for Conservation of Nature (IUCN), 87% have been categorized as least concern, 7% near threatened, 3% endangered and 3% vulnerable. We proceeded to perform the calculation of the Sorense index, which allows to determine the similarity in the study areas, obtaining a 76.92%, indicating that much of the species can be observed in the two monitored locations, this information being considered for the generation of the bird guide of the canton, so that if people want to see a particular species they can approach each of the sites in a concrete way. This research has been systematized in a descriptive photographic guide, as a means of disseminating the results obtained. It can be concluded that the study area despite being intervened, has species of birds, which can be used touristically, and therefore it is recommended that research on avifauna be increased and deepened in order to generate an avitouristic route and that this becomes a sustainable activity that promotes development in the locality.